1998
DOI: 10.1128/jb.180.12.3137-3143.1998
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Growth, a Property Horizontally Transferred by an Hfr-Like Mechanism among Extreme Thermophiles

Abstract: Despite the fact that the extreme thermophilic bacteria belonging to the genus Thermus are classified as strict aerobes, we have shown that Thermus thermophilus HB8 (ATCC 27634) can grow anaerobically when nitrate is present in the growth medium. This strain-specific property is encoded by a respiratory nitrate reductase gene cluster (nar) whose expression is induced by anoxia and nitrate (S. Ramı́rez-Arcos, L. A. Fernández-Herrero, and J. Berenguer, Biochim. Biophys. Acta, 1396:215–1997). We show here that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 26 publications
2
39
0
Order By: Relevance
“…1C). It is important to note that the proteins were not detected in the aerobic strain HB27 (lane 27), whereas they were identified in its nitrate-respiring derivative HB27c (lane 27c), which was obtained by conjugation with the NAR1 strain (Ramírez-Arcos et al, 1998b), demonstrating that the drp genes were co-transferred along with the nar operon. In conclusion, DrpA and DrpB were shown to be actual proteins expressed in most nitraterespiring strains of T. thermophilus.…”
Section: Conserved Genes Are Encoded Downstream the Respiratory Nrmentioning
confidence: 98%
See 1 more Smart Citation
“…1C). It is important to note that the proteins were not detected in the aerobic strain HB27 (lane 27), whereas they were identified in its nitrate-respiring derivative HB27c (lane 27c), which was obtained by conjugation with the NAR1 strain (Ramírez-Arcos et al, 1998b), demonstrating that the drp genes were co-transferred along with the nar operon. In conclusion, DrpA and DrpB were shown to be actual proteins expressed in most nitraterespiring strains of T. thermophilus.…”
Section: Conserved Genes Are Encoded Downstream the Respiratory Nrmentioning
confidence: 98%
“…Thermus thermophilus is one of the cases in which no nitrate-sensing homologues have been identified, though some strains of this phylogenetically ancient bacterium can use nitrogen oxides as electron acceptors in anaerobic conditions (Cava et al, 2008). In T. thermophilus NAR1, nitrate is reduced only to nitrite allowing its anaerobic growth (Ramírez-Arcos et al, 1998b). This capability is encoded by a mobile genetic element (NCE, Nitrate Respiration Conjugative Element) (Cava et al, 2007), which includes at least three operons.…”
Section: Introductionmentioning
confidence: 99%
“…Seven T. thermophilus isolates were analysed for their ability to grow anaerobically with nitrate and nitrite, in comparison with an aerobic control (HB27) and two partially denitrifying strains, the NAR1 strain, in which the NCE was initially described (Ramirez-Arcos et al, 1998a), and the HB27c strain, a derivative of HB27 that contains the NCE (Ramirez-Arcos et al, 1998b).…”
Section: Denitrification In T Thermophilusmentioning
confidence: 99%
“…However, there are exceptions, namely the NAR1 strain of Thermus thermophilus that only express the Nar reductase, in such a way that nitrite accumulates in the growth medium as the final product (Ramirez-Arcos et al, 1998a). This partial denitrification is encoded by a conjugative element (nitrate conjugative element, NCE) that can be transferred to strictly aerobic strains of the same species, allowing the aerobic receptor strain to grow as a facultative anaerobe (Ramirez-Arcos et al, 1998b). The NCE encodes two main operons, nar and nrc, and the regulatory transcription factors DnrS and DnrT required for their expression under anaerobic condition with nitrate as well (Ramirez-Arcos et al, 1998b;Cava et al, 2004;Cava and Berenguer, 2006) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, Thermus thermophilus HB8, which produces a nitrate reductase enzymatic complex, is able to grow in anaerobic conditions in the presence of nitrate. Also, it was reported that the strictly aerobic T. thermophilus HB27 can incorporate this ability by plasmidic conjugation (24).…”
Section: Introductionmentioning
confidence: 99%